Enseñanza de la Topología y Geometría en los niveles elementales - Vidal Costa, E.; Torre Fernández, E. de la (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
Both topological and geometric notions are a particularly essential component in the development of children's awareness. Many authors agree in the importance of this knowledge but are in dispute as to how it should be structured. We are dividing the work into two parts: in the first we are dealing with the content and offering a learning scheme; in the second we are offering some didactic guidance.